Rational design of a large Stokes shift xanthene–benzothiozolium dyad for probing cysteine in mitochondria. Issue 8 (7th February 2022) - Cai, Songtao; Liu, Qiuchen; Liu, Chang; He, Song; Zhao, Liancheng; Zeng, Xianshun; Gong, Jin
Abstract : We provided an effective strategy to effectively improve the Stokes shift of xanthene–benzothiozolium fluorophores. Abstract : Xanthene-modified cyanine dyes are considered to be an effective means to extend the emission wavelength and improve the photo-stability of cyanine dyes. However, the fluorophores obtained by this strategy generally have narrow Stokes shifts, which severely limits their application in biological imaging. Herein, a reasonable design strategy is adopted to provide an effective strategy to commendably improve the Stokes shift of xanthene–benzothiozolium fluorophores via the simultaneous expansion of a molecular π-conjugated system and heteroatomic substitution. Combined with density functional theory calculation guidance, the O atom is replaced with the S atom in the xanthene moiety and a π-conjugated benzene ring is introduced in the benzothiozolium moiety. Surprisingly, the results of the spectroscopic experiment showed that the fluorescence emission wavelength of PhCy-OH was extended to 803 nm, and the Stokes shift was improved to 68 nm. PhCy-Cys can effectively distinguish Cys from homocysteine (Hcy) and glutathione (GSH) with an extremely low detection limit of 0.166 μM. Importantly, PhCy-Cys has the ability to image endogenous Cys in mitochondria, providing the potential for exploring the specific function and mechanism of Cys in regulating oxidative stress in mitochondria.